2014
DOI: 10.1134/s1070428014110190
|View full text |Cite
|
Sign up to set email alerts
|

Ratio of 1,3- and 1,5-dialkyl-substituted pyrazoles obtained from chlorovinyl alkyl ketones and alkylhydrazines, 3(5)-pyrazoles and alkyl bromides

Abstract: Unsymmetrically substituted 1,3-and 1,5-dialkylpyrazoles and 1,3-dialkyl-5-chloropyrazoles were prepared. 2-Chlorovinyl ketones react with С 1 -С 8 -alkylhydrazines along two routes giving mixtures of 1-R'-3-R-and 1-R'-5-R-pyrazoles with the prevalence of 1,3-isomer. The proportion of 3-substituted 1-alkylpyrazole in the isomers mixture grows from 60 to 94-97% with growing length of the alkyl chain in the hydrazine. The alkylation of 1-unsubstituted 3(5)-alkylpyrazoles with alkyl bromides afforded predominantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
4
0
1
Order By: Relevance
“…The mass spectrum was recorded on a DFS (Thermo Electron) high-resolution mass spectrometer. The synthesis of 1-methyl-3-ethyl-1 H -pyrazole and a mixture of 1-butyl-3(5)-ethyl-1 H -pyrazoles was described elsewhere, , respectively. 4-Formylpyrazoles were prepared by the procedure reported elsewhere …”
Section: Experimental Sectionmentioning
confidence: 99%
“…The mass spectrum was recorded on a DFS (Thermo Electron) high-resolution mass spectrometer. The synthesis of 1-methyl-3-ethyl-1 H -pyrazole and a mixture of 1-butyl-3(5)-ethyl-1 H -pyrazoles was described elsewhere, , respectively. 4-Formylpyrazoles were prepared by the procedure reported elsewhere …”
Section: Experimental Sectionmentioning
confidence: 99%
“…It has been previously shown that the reaction of butyryl chloride with ethyne in CH 2 Cl 2 in the presence of AlCl 3 as a catalyst affords 1‐chlorohex‐1‐en‐3‐one 1 in 66% yield (Scheme 1). 34 …”
Section: Resultsmentioning
confidence: 99%
“…It has been previously shown that the reaction of butyryl chloride with ethyne in CH 2 Cl 2 in the presence of AlCl 3 as a catalyst affords 1-chlorohex-1-en-3-one 1 in 66% yield (Scheme 1). 34 In this work, we carried out the reaction of butyryl chloride with ethynylbenzene under the same conditions. The expected 1-chloro-1-phenylhex-1-en-3-one 2 was obtained as a mixture of the Z/E isomers in a ratio of 10/1 in 71% yield.…”
Section: Synthesismentioning
confidence: 99%
“…The known methods for obtaining these practically important substances are complex and multi-stage, while the yields of the final products are low [100,101]. As a result of the search for new ways of recycling rocket fuel, as mentioned above, we have proposed an original method for the formation of functionally substituted pyrazoles or isoxazoles using heptyl (or hydroxylamine) or other reagents [102][103][104][105][106][107][108][109][110][111][112].…”
Section: Organylpyrazole Derivativesmentioning
confidence: 99%